Examining the associations between PTSD symptoms and aspects of emotion dysregulation through network analysis. (March 2022) - Haws, James Kyle; Brockdorf, Alexandra N.; Gratz, Kim L.; Messman, Terri L.; Tull, Matthew T.; DiLillo, David
Abstract: Despite the clearly established link between posttraumatic stress disorder (PTSD) and emotion dysregulation, little is known about how individual symptoms of PTSD and aspects of emotion dysregulation interrelate. The network approach to mental health disorders provides a novel framework for conceptualizing the association between PTSD and emotion dysregulation as a system of interacting nodes. In this study, we estimated the structural relations among PTSD symptoms and aspects of emotion dysregulation within a large sample of women who participated in a multi-site study of sexual revictimization ( N = 463). We estimated expected influence to reveal differential associations among PTSD symptoms and aspects of emotion dysregulation. Further, we estimated bridge expected influence to identify influential nodes connecting PTSD symptoms and aspects of emotion dysregulation. Results highlighted the key role of concentration difficulties in expected influence and bridge expected influence. Findings highlight several PTSD symptoms and aspects of emotion dysregulation that may be targets for future intervention. Highlights: Examined the differential associations between PTSD symptoms and aspects of emotion dysregulation. Concentration difficulties emerged as an influential node. Discussed avenues to target concentration difficulties to produce therapeutic cascades.